Penerapan Strategi Freemium pada Aplikasi Permainan Ponsel Online - Sabella, Joanna Jessica (Jurnal InterAct, 2021)
The number of smartphone users are significantly increasing as the technology developed. Many people use their smartphone to play online games. Mobile Legends: Bang Bang (MLBB) is one of the online games that has a lot of users, especially in Indonesia. MLBB is developed by Moonton, which uses freemium strategy to promote their game on applications store. This research’s objective is to find the freemium strategy’s effectivity and other important factors that increase the application’s in-app purchase. The methodology approach of this research is qualitative method. The data were collected by doing literature review and interview. The collected data were processed by coding technique. The research’s result shows that freemium strategy and other important factors could increase users’ in-app purchase intention.